Ultrasonic waves in some biological suspensions and emulsions - LEWANDOWSKI, J. (Archives of Acoustics, 1992)
The frequency dependence is established for the propagation velocity and attenuation coefficient of ultrasonic waves in dilute suspensions and emulsions and digital computations are performed for the aqueous emulsion of sunflower oil. The results show that the measurements of the propagation velocity of ultrasonic waves enable us to estimate the volume fraction of the suspended particles of both dilute and highly concentrated suspensions and emulsions. Keywords: suspensions, emulsions, ultrasonic waves, propagation velocity, attenuation coefficient.